The Prevalence of Misophonia and Its Relationship with Obsessive-compulsive Disorder, Anxiety, and Depression in Undergraduate Students of Shiraz University of Medical Sciences: A Cross-Sectional Study - Shahrzad Yektatalab; Agrin Mohammadi; Ladan Zarshenas (Shiraz University of Medical Sciences, 2022)
Background: Misophonia is a severe emotional response to repetitive sounds. This disorder may limit a person's communication, reduce his/her ability, or disrupt his/her social and personal life. This study aimed to determine the prevalence of Misophonia and its relationship with obsessive-compulsive disorder, anxiety, and depression in undergraduate students of Shiraz University of Medical Sciences.Methods: The present study is an analytical descriptive study conducted in October 2020. The study samples consisted of 390 undergraduate students of Shiraz University of Medical Sciences. A relative and systematic sampling method was used. In this study, demographic questionnaire, misophonia questionnaire (A score of 7 or higher is considered as misophonia), Beck anxiety questionnaire, Beck depression questionnaire, and Maudsley obsessive-compulsive inventory questionnaire were used, and the data were analyzed using SPSS 24 software. In this study, chi-square test was used to examine the relationship between the variables. Due to the non-normality of the data, the Spearman correlation coefficient was used for data analysis. The significance level was considered equal to and less than 0.05.Results: Of the 390 participants in the study, 93 (23.8%) had experienced misophonia. Among these 93 students, 37 (39.8%) had obsessive-compulsive disorder, 8 (8.6%) suffered anxiety, and 9 (9.7%) were depressed. There was a significant and direct relationship between misophonia and obsessive-compulsive disorder,anxiety and depression respectively(P<0.001).Conclusion: Due to the prevalence of misophonia among students and its direct relationship with obsessive-compulsive disorder, anxiety and depression, we recommend that future studies should be conducted to find the ways to prevent and reduce the incidence of misophonia.